La Grèce, pas si balkanique que ça - Michel Sivignon (EchoGéo)
In Greece the riots which bursted on December 6th after the death of a youth killed by a policeman and are going on show the deep difficulties which the Greek society must face . These difficulties are related to local archaisms in Greek society and overall to a very fast integration into the European Union and to the constraints of globalisation. In these respects, young people are deeply concerned: it is very difficult for them to escape unemployment